Optical studies of as-deposited and annealed Cu₇GeS₅I thin films - Studenyak, I.P.; Bendak, A.V.; Rybak, S.O.; Izai, V.Yu.; Kúš, P.; Mikula, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Cu₇GeS₅I thin films were obtained by non-reactive radio frequency magnetron sputtering onto silicate glass substrates. Optical transmission spectra of as-deposited and annealed Cu₇GeS₅I thin films were measured in the temperature interval 77–300 K. The temperature behaviour of Urbach absorption edge and dispersion of refractive index for as-deposited and annealed Cu₇GeS₅I thin films was analyzed. Influence of annealing on the optical parameters and disordering processes in Cu₇GeS₅I thin films was studied.